Barriers to Utilization of Antenatal Care Services in Eastern Nepal - Deo, Krishna Kumar; Paudel, Yuba Raj; Khatri, Resham Bahadur; Bhaskar, Ravi Kumar; Paudel, Rajan; Mehata, Suresh; Wagle, Rajendra Raj (Frontiers in Public Health, 2015)
Background World Health Organization recommends at least four pregnancy check-ups for normal pregnancies. Ministry of Health and Population Nepal has introduced various strategies to promote prenatal care and institutional delivery to reduce maternal and child deaths. However, maternal health service utilization is low in some selected socio-economic and ethnic groups. Hence, this study aims to assess barriers to the recommended four antenatal care (4ANC) visits in eastern Nepal. Methods A cross-sectional quantitative study was conducted in Sunsari district. A total of 372 randomly selected women who delivered in the last year preceding the survey were interviewed using a semi-structured questionnaire. Bivariate and multivariate logistic regression analysis was carried out to identify barriers associated with 4ANC visits. Results More than two-third women (69%) attended at least 4ANC visits. The study revealed that women exposed to media had higher chance of receiving four or more ANC visits with an adjusted odds ratio (aOR = 3.5, 95% CI: 1.2–10.1) in comparison to women who did not. Women from an advantaged ethnic group had more chance of having 4ANC visits than respondents from a disadvantaged ethnic group (aOR = 2.4, 95% CI: 2.1–6.9). Similarly, women having a higher level of autonomy were nearly three times more likely (aOR = 2.9, 95% CI: 1.5–5.6) and richer women were twice (aOR = 2.3, 95% CI: 1.1–5.3) as likely to have at least 4ANC visits compared to women who had a lower level of autonomy and were economically poor. Conclusion Being from disadvantaged ethnicity, lower women’s autonomy, poor knowledge of maternal health service and incentive upon completion of ANC, less media exposure related to maternal health service, and lower wealth rank were significantly associated with fewer than the recommended 4ANC visits. Thus, maternal health programs need to address such socio-cultural barriers for effective health care utilization.